Prenatal stress, genomic variations and recurrent respiratory tract infections - the FinnBrain Birth Cohort Study - Korhonen, Laura (fi=Turun yliopisto|en=University of Turku|, 2020)
Risk profiles associated with many diseases are formed at a very early stage of development, which occur before birth. Exposure of the fetus to maternal psychological distress during pregnancy may alter fetal biology and thus predispose the fetus to subsequent illnesses such as childhood recurrent respiratory infections. This dissertation is part of the FinnBrain Birth Cohort Study, which recruited 3808 families between years 2012–2015. This prospective cohort-based study followed the symptoms of anxiety and depression in mothers, partnership satisfaction and the occurrence of children’s recurrent respiratory tract infections from the 14th week of pregnancy until the child was two years old. Our aim was to investigate whether there was an association between maternal prenatal psychological distress and the occurrence of the child’s recurrent respiratory tract infections. In a smaller subset of the Cohort, we investigated the association of maternal prenatal psychological distress on cortisol production in 10-week-old children. We also investigated the relationship between genetic susceptibility to respiratory infections and the interaction between genetic susceptibility and maternal prenatal psychological distress. In this study, it was shown that in addition to the previously known risk factors (e.g. the number of siblings, shorter duration of breastfeeding), maternal prenatal psychological distress was associated with an increased risk for recurrent respiratory infections in children. In addition, we found that in children, whose mothers had prenatal psychological distress, had a reduced cortisol response in the stress test depending on if the child had a concomitant rhinovirus infection. Genetic variations in the IFI44L gene, part of the type I interferon pathway, associated with an increased susceptibility to respiratory infections and acute otitis media. Interleukin-6 gene variations were associated with an increased risk for recurrent respiratory infections. There was no interaction between these genetic predispositions and maternal stress during pregnancy, but sex differences were noted. This work provides new preventive strategies for recurrent upper respiratory tract infections in children and offers new insights into the interactions between stress and immune systems

Raskaudenaikainen stressi, geneettiset variaatiot ja toistuvat hengitystieinfektiot- FinnBrain-syntymäkohorttitutkimus Sairauksien riskiprofiili voi muodostua jo ennen syntymää. Sikiön altistuminen äidin psykologiselle stressille raskauden aikana saattaa muuttaa sikiön biologiaa altistaen myöhemmille sairauksille kuten toistuville hengitystieinfektioille. Väitöskirja on osa FinnBrain-syntymäkohorttitutkimusta, johon on rekrytoitu 3808 perhettä vuosina 2012–2015. Tässä prospektiivisessa syntymäkohortissa seurattiin äitien ahdistus- ja masennusoireita, parisuhdetyytyväisyyttä 14. raskausviikolta siihen asti, kun lapsi oli kahden vuoden ikäinen. Myös tiedot lapsien toistuvista hengitystieinfektioista kerättiin. Tavoitteenamme oli tutkia äidin raskaudenaikaisen stressin (masennus–ja ahdistusoireilun) yhteyttä lapsen riskiin sairastaa toistuvia hengitystieinfektioita. Pienemmässä kohortin osajoukossa tutkimme äidin raskaudenaikaisen stressin vaikutusta 10 viikon ikäisten lasten kortisolin tuotantoon stressikokeessa. Tutkimme myös geneettistä alttiutta hengitystieinfektioille ja geneettisen alttiuden sekä äidin raskaudenaikaisen stressin yhteisvaikutusta. Tässä tutkimuksessa osoitettiin, että jo tunnettujen riskitekijöiden (esim. sisarusten lukumäärä, imetyksen lyhyempi kesto) lisäksi äidin raskaudenaikainen stressi oli yhteydessä lapsen suurentuneeseen riskiin sairastaa toistuvia hengitystieinfektioita. Lisäksi havaitsimme, että lapsilla, joiden äideillä oli ollut raskausaikana stressioireita, todettiin alentunut kortisolivaste stressikokeessa, mikäli lapsella oli samanaikainen rinovirusinfektio. Geneettiset vaihtelut tyypin I interferonivasteeseen liittyvässä IFI44L-geenissä lisäsivät alttiutta hengitystieinfektioille ja välikorvatulehduksille. Interleukiini 6-geenin polymorfismi liittyi lapsen lisääntyneeseen riskiin sairastaa toistuvia hengitystieinfektioita. Näillä geneettisillä alttiuksilla sekä äidin raskaudenaikaisella stressillä ei todettu yhteisvaikutusta, mutta sukupuolieroja havaittiin. Tämä tutkimus tuo uutta tietoa lasten toistuvien hengitystieinfektioiden ennaltaehkäisyyn sekä tuo tietoa stressinsäätely- ja immuunipuolustusjärjestelmien välisen vuorovaikutuksen kehittymisestä.